A CASE STUDY OF CAT STERILIZATION IN KARANGWUNI, YOGYAKARTA: IMPACTS PERCEIVED BY CARETAKERS AND THEIR UNDERSTANDING OF THE PROGRAM - Putri, Khalisya Anjani; Tippy, Winaya Satasya; Viary, Janice (Buletin Veteriner Udayana; Vol. 15 No. 5 Oktober 2023, 2023)
There is yet to be collected the number of cats in Indonesia, including free- roaming cats. Studies have shown that there is a connection between sterilization and free-roaming cats’ health and welfare. In 2021, Suara Suaka Indonesia decided to hold a small-scale sterilization program in a neighborhood called Karangwuni, Yogyakarta to contribute in lowering cat population. In this case study, we focus on the effect of sterilization to cats that are perceived by humans. Survey was done using Google Forms, taking information on their demographics, involvement with Suara Suaka Indonesia, feedback on their cats’ post-surgery changes and their understanding on sterilization. Respondents are generally satisfied with the impact sterilization has on them and their cats, this is supported by how they perceive sterilization as important and their willingness to recommend the procedure to other people. However, there can still be improvement on delivering messages of sterilization to ensure that the purpose, process, and impact of sterilization can be adequately understood by all participants of the program.